Prospects for using amortized coatings obtained by the method of gas-thermal spraying, for the creation of protective electromagnetic screens - Куницький, Ю. А.; Волошенко, А. С. (Proceedings of National Aviation University (archive), 2002)
The amorphous coatings, which have high shielding properties, are considered to provide technical protection of information. Requirements for technology are defined manufacturing of amorphous coatings on the basis of analysis of the conditions of their operation and purpose